Assessing dental hygiene students' readiness for interprofessional learning and collaborative practice. Issue 6 (24th February 2020) - Kanji, Zul; Lin, Diana; Karan, Jelena
Abstract: Purpose: The need for interprofessional education (IPE) has been well documented and communicated by many prominent governmental bodies and health organizations. However, more longitudinal outcomes research is needed to demonstrate the impact of IPE on students' attitudes and behaviors. This study assessed dental hygiene students' readiness for IPE and collaborative practice at the University of British Columbia, Canada. Methods: A modified Readiness for Interprofessional Learning Scale (RIPLS) survey was conducted on 23 (96% response rate) second‐year dental hygiene students prior to commencing the university's newly integrated 4‐week IPE curriculum and immediately following its completion 1 month later. A focus group comprising 5 students then explored learning experiences and impact on attitudes about collaborative practice in greater depth. Curriculum content included professionalism, ethical practice, Indigenous cultural safety, and resiliency. Results: Attitudinal shifts were observed in 3 of the RIPLS measures suggesting that students found greater clarity regarding their professional roles and became more receptive to learning clinical problem‐solving skills with other disciplines. No statistically significant differences surfaced between the pre‐attitudinal and post‐attitudinal RIPLS measures. The focus group revealed 3 prominent themes: greater role clarification, recognition of similarities in knowledge and practice with other professions, and cultivation of professional identity, collegiality, and respect. Conclusion: Students found greater clarity about professional roles and developed an enhanced appreciation for working with other health professions after completing the university's month‐long integrated IPE curriculum.